Competition for a single resource and coexistence of several species in the chemostat - Nahla Abdellatif; Radhouane Fekih-Salem; Tewfik Sari (Mathematical Biosciences and Engineering)
We study a model of the chemostat with several species in competition for a single resource.We take into account the intra-specific interactions between individuals of the same population of micro-organisms andwe assume that the growth rates are increasing and the dilution rates are distinct.Using the concept of steady-state characteristics, we present a geometric characterization of the existence and stability of all equilibria.Moreover, we provide necessary and sufficient conditions on the control parameters of the system to have a positive equilibrium.Using a Lyapunov function, we give a global asymptotic stability result for the competition model of several species.The operating diagram describes the asymptotic behavior of this model with respect to control parametersand illustrates the effect of the intra-specific competition on the coexistence region of the species.